Оцінювання і вибір оптимальної форми державно-приватного партнерства для ЛКП «Залізничнетеплоенерго» - Михальчишин, Н. Л.; Демків, О.-І. М. (Видавництво Львівської політехніки, 2014)
Обґрунтовано недостатність наявності конкурентних відносин на певних товарних ринках національної економіки для забезпечення максимально можливого рівня ефективності діяльності підприємств, що зумовлює необхідність функціонування ринків у стані природних монополій. Зазначено, що недоцільність відмови від функціонування ринку в стані природної монополії зумовлює потребу дослідити можливості підвищення ефективності таких структур через застосування альтернативних до конкурентного тиску механізмів, одним із яких є державно-приватне партнерство. Описано особливості проходження етапів визначення оптимальної форми державно-приватного партнерства, якими є аналіз проблем функціонування конкретних суб’єктів природних монополій, дослідження особливостей кожної з форм державно-приватного партнерства, оцінювання здатності форм державно-приватного партнерства усунути наявні на підприємстві прояви неефективності. Встановлено оптимальну для досліджуваного підприємства форму державно-приватного партнерства, яка може впроваджуватись на місцевому та загальнодержавному рівнях. В результаті дослідження визначено, що, за умов застосування індивідуального підходу до вибору форми державно-приватного партнерства та збереження необхідного рівня впливу органів державної влади та органів місцевого самоврядування на діяльність суб’єкта господарювання, державно-приватне партнерство є ефективним механізмом мінімізації проявів проблем неефективності суб’єктів господарювання, що функціонують на ринках природних монополій та на суміжних ринках. In the article lack of availability of competitive relations in certain commodity markets of the national economy to ensure maximum possible efficiency of enterprises, which necessitates the functioning of markets in a state of natural monopoly, was justified. Under certain conditions, only this type of market model makes it possible to minimize the price level and optimize production costs. It was determined that despite the growth of enterprises activity indicators in the monopoly market structure, potential of improving the efficiency of these markets compared with the competitive structure are not fully implemented. It was noted that the lack of appropriateness of failure of market functioning in a state of natural monopoly makes it necessary to study the possibility of increasing the efficiency of these structures through the use of alternative mechanisms to competitive pressures, one of which is a public-private partnership. Features of passage stages determine the optimal form of public-private partnerships, that include analysis of specific problems of the natural monopolies, studying the characteristics of each form of public-private partnerships, evaluating the ability of publicprivate partnerships to eliminate existing inefficiency problems and determination from results of the analysis of the optimal shape, were described. Main problems functioning LME “Zaliznychneteploenerho” according to the components of the internal environment, were identified and systematized based on the analysis of financial and statistical reports, analysis of the company activity. Influence the factors of external environment on enterprise, such as belonging to communal ownership and natural monopolies, the impact of public policy on regulation of natural monopolies and entities operating in related markets, were characterized. Public-private partnerships as a tool for solving problems of the natural monopolies have been characterized. The most common forms of public-private partnerships with their features such parameters as the term agreement, obligations of the parties, the distribution of risk, advantages and disadvantages, etc. have been described. Evaluation of the ability of each form of public-private partnerships to solve any problems LME “Zaliznychneteploenerho” activities was conducted. Inability to use the following types of contractual alternatives as privatization, lease agreements, contracts for services and contracts management through weighty social value of the entity and the need for the involvement of private investment, has been set based on evaluation of public-private partnerships. The optimal form of public-private partnership for the sampled enterprises, which can be implemented at the local and national levels, was established. As a result of the study it was determined that, through the use of an individual approach to the choice of the form of public-private partnerships and maintaining the required level of impact of state and local governments to the activities of the entity, public-private partnerships are an effective mechanism to minimize the manifestations of problems ineffectiveness of entities operating in the markets of natural monopolies and in adjacent markets.
Evaluation and selection of optimal form of public-private partnerships for the LME “Zaliznychneteploenerho”
Keywords: природна монополія; суміжний ринок; неефективність природної монополії; державно-приватне партнерство; natural monopoly; related market; inefficiency of natural monopoly; publicprivate partnerships